Phycoremediation Using Microalgae Chlorella vulgaris and Nannochloropsis oculata to Remove Lead Heavy Metals - Nafi'ah, Chia Fifin; Cahyonugroho, Okik Hendriyanto (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Heavy metals are pollutant parameters that contain high toxicity and are dangerous which can accumulate in the tissues of living things. One of the heavy metals contained in wastewater is lead (Pb). This metal is included in the extremely toxic category which can cause health problems. One way to treat waste containing the heavy metal Pb is by bioremediation using microalgae (phycoremediation). In this study, phycoremediation used the microalgae Chlorella vulgaris and Nannochloropsis oculata, as well as a consortium of both. This study aims to determine the ability of each microalga and the consortium of the two microalgae in removing lead heavy metals. The phycoremediation potential was measured based on the ratio of microalgae varied (100:0, 50:50, and 0:100) and the concentration of Pb waste (1, 5, and 10 mg/L) within 14 days on a batch scale. The results showed that the microalgae Chlorella vulgaris in reactor 10B (100% Chlorella vulgaris, 0% Nannochloropsis oculata) was able to remove 85.0% from a concentration of 10 mg/L to 1,5 mg/L.